Assessment of the Economic Pillar and Environmental Pillar of Sustainable Development in the European Union - Huttmanová, Emília; Valentiny, Tomáš (European Journal of Sustainable Development, 2019)
Sustainability is currently being implemented in a variety of activities. In practice, however, its achievement is complicated and difficult. In the process of achieving sustainability, it is essential to know the components of sustainable development and their current state. In general, sustainable development is perceived through four pillars - economic, social, environmental and institutional. In some cases, however, achieving a positive result in one of them could cause negative results in other(s). This inverse relationship can also be identified in the case of the economic and environmental pillar of sustainable development. The complexity of pillar´s relations is one of the factors which causes considerable complicated achievement of sustainability. The difference of the individual pillars of sustainable development and difference in the individual European Union countries development (despite their relative homogeneity) is an object of our interest. The aim of the paper is to evaluate the current state and development of the economic and environmental pillar of sustainable development in EU countries, using selected indicators. Keywords: sustainability, sustainable development, economic pillar, environmental pillar